Opioid-induced hypernociception is associated with hyperexcitability and altered tetrodotoxin-resistant Na(+) channel function of dorsal root ganglia - Ross, Gracious R. (American Physiological Society, 2012)
Opiates are potent analgesics for moderate to severe pain. Paradoxically, patients under chronic opiates have reported hypernociception, the mechanisms of which are unknown. Using standard patch-clamp technique, we examined the excitability, biophysical properties of tetrodotoxin-resistant (TTX-R) Na(+) and transient receptor potential vanilloid 1 (TRPV1) channels of dorsal root ganglia neurons (DRG) (L(5)–S(1)) from mice pelleted with morphine (75 mg) or placebo (7 days). Hypernociception was confirmed by acetic acid-writhing test following 7-day morphine. Chronic morphine enhanced the neuronal excitability, since the rheobase for action potential (AP) firing was significantly (P < 0.01) lower (38 ± 7 vs. 100 ± 15 pA) while the number of APs at 2× rheobase was higher (4.4 ± 0.8 vs. 2 ± 0.5) than placebo (n = 13–20). The potential of half-maximum activation (V(1/2)) of TTX-R Na(+) currents was shifted to more hyperpolarized potential in the chronic morphine group (−37 ± 1 mV) vs. placebo (−28 ± 1 mV) without altering the V(1/2) of inactivation (−41 ± 1 vs. −33 ± 1 mV) (n = 8–11). Recovery rate from inactivation of TTX-R Na(+) channels or the mRNA level of any Na(+) channel subtypes did not change after chronic morphine. Also, chronic morphine significantly (P < 0.05) enhanced the magnitude of TRPV1 currents (−64 ± 11 pA/pF) vs. placebo (−18 ± 6 pA/pF). The increased excitability of sensory neurons by chronic morphine may be due to the shift in the voltage threshold of activation of TTX-R Na(+) currents. Enhanced TRPV1 currents may have a complementary effect, with TTX-R Na(+) currents on opiate-induced hyperexcitability of sensory neurons causing hypernociception. In conclusion, chronic morphine-induced hypernociception is associated with hyperexcitability and functional remodeling of TTX-R Na(+) and TRPV1 channels of sensory neurons.